Detection of programmed death ligand 1 protein and CD8+ lymphocyte infiltration in plurihormonal pituitary adenomas: A case report and review of the literatures. Issue 49 (December 2017) - Wang, Pengfei; Wang, Tingjian; Yang, Yakun; Yu, Chunjiang; Liu, Ning; Yan, Changxiang
Abstract: Rationale: Pituitary adenomas secreting two or more hormones were referred to the plurihormonal tumors. The management of this type of the tumor was tumor resection and amelioration of the unbalanced hormones. However, it washard to cure the plurihormonal adenomas, as they were usually refractory to the traditional treatment. New therapeutic methods were needed in dealing this tumor. Patient concerns: In this report, we described a patient who suffered from plurihormonal pituitary adenomas, with concomitant prolactin (PRL) and growth hormone (GH) secretion. The adenomas showed aggressive behaviors, which was giant, invasive, and refractory to bromocriptine treatments. Interventions: The patient underwent a surgical treatment. Diagnosis: The pathology together with clinical presentation and blood hormone test confirmed that it was PRL-GH secreting tumors. Outcomes: Although a gross resection was achieved, the postoperative hormones were not normalized. There were also abundant programmed death ligand-1 proteins and CD8 + lymphocyte infiltration in the tumor tissues. Lessons: Our results indicated immunotherapy as a promising treatment for this tumor. More studies were needed to investigate the possibility of the immunotherapy in pituitary adenomas. Abstract : Supplemental Digital Content is available in the text